2022
DOI: 10.1038/s41386-022-01297-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of the acute effects of lysergic acid diethylamide and psilocybin in a double-blind placebo-controlled study in healthy subjects

Abstract: Growing interest has been seen in using lysergic acid diethylamide (LSD) and psilocybin in psychiatric research and therapy. However, no modern studies have evaluated differences in subjective and autonomic effects of LSD and psilocybin or their similarities and dose equivalence. We used a double-blind, randomized, placebo-controlled, crossover design in 28 healthy subjects (14 women, 14 men) who underwent five 25 h sessions and received placebo, LSD (100 and 200 µg), and psilocybin (15 and 30 mg). Test days w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
141
2
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 48 publications
17
141
2
4
Order By: Relevance
“…LSD may produce acute anxiety in some people, particularly at high doses (4,20). Specifically, effects of LSD at the dose and formulation that were used in the present study have been characterized very well in healthy subjects, and the dose could be considered high and have a greater risk of acute anxiety (4,6). Transient anxiety and confrontation with a fear of death were also reported in the pilot study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…LSD may produce acute anxiety in some people, particularly at high doses (4,20). Specifically, effects of LSD at the dose and formulation that were used in the present study have been characterized very well in healthy subjects, and the dose could be considered high and have a greater risk of acute anxiety (4,6). Transient anxiety and confrontation with a fear of death were also reported in the pilot study.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, acute LSD effects last longer compared to those of psilocybin. However, a recent study documented otherwise comparable acute subjective effects and tolerability of LSD and psilocybin in healthy subjects (6). In the 1950s to 1970s, LSD was used in patients with endstage cancer to improve mood and reduce anxiety (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Though ayahuasca increased BDNF levels in both healthy and depressed people in one study, another found no change [46,47]. Several studies have measured the effects of LSD on BDNF, with some finding an increase [48,49] and others no change [50,51]. In two studies in healthy subjects, comparable doses of psilocybin did not elevate plasma BDNF in one [50], but did so in the other [52].…”
Section: Do Psychedelics Enhance Neuroplasticity?mentioning
confidence: 88%
“…Sub-hallucinogenic doses of between 5 and 20 µg LSD produced significant short-term enhancements in plasma BDNF [48]. However, a similar study using doses of between 25 µg and 200 µg LSD only found significant effects on BDNF at 200 µg [49], and another failed to find significant changes even at this dose [50]. Perhaps using different methods, future research should seek to clarify the minimum and optimal doses for stimulating neuroplasticity with different psychedelics.…”
Section: Hippocampusmentioning
confidence: 98%
See 1 more Smart Citation